Households and Homes. Changing Household Composition and the Dutch Housing Market - Dekker,Catharina Helena (2024)
The public debate about the housing crisis in the Netherlands is more heated than ever before. Therefore, the aim of this thesis is to examine the effect of changing household structures on the Dutch housing market by taking a mixed-methods approach. By combining existing quantitative data and literature with new qualitative data from a conducted survey, the challenges on the housing market in relation to changing households between 1995 and 2022 are mapped out. The study shows that the composition of households has changed and that the number of households has grown significantly as a result of population growth, household dilution and immigration. Due to numerous regulations and policies, the qualitative and quantitative housing supply cannot keep up with the increase in the number of households. Additionally, the poor flow on the housing market and the costs of housing are perceived as major challenges on the Dutch housing market.